The relationship of personality and trait anxiety between male and female volleyball players - Patsiaouras, A.; Chatzidimitriou, M.; Charitonidis, K.; Giota, A.; Kokaridas, D. (Annals of Applied Sport Science, 2017)
Objectives. The purpose of the study was to examine possible correlations and differences of personality and trait anxiety between male and female volleyball players. Methods. The sample consisted of 79 Division A & C volleyball athletes (35 men and 44 women). Personality factors were investigated with the use of IPIP (International Personality Item Pool), whereas for trait anxiety the STAI - X2 (State - Trait Anxiety Inventory) questionnaire was used. Results. Statistically important differences were noticed between male and female volleyball players regarding the factors of extraversion, agreeableness, and emotional stability. In the remainder examined factors, that is, trait anxiety, consciousness and intellectual ability-imagination, no statistically important differences were noticed. A differentiation was also noticed regarding the relationship of factors when gender was selected as a criterion. Conclusion. The results reveal that male athletes were influenced to a different degree on personality factors as compared to female athletes. Further research is needed to investigate differences between the two genders by using samples from other team and individual sports.